Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Let y=x
x
+x
a
+a
x
+a
a
Also let, x
x
=u,x
a
=v,a
x
=w, and a
a
=s
∴y=u+v+w+s
⇒
dx
dy
=
dx
du
+
dx
dv
+
dx
dw
+
dx
ds
.....(1)
u=x
x
⇒logu=logx
x
⇒logu=xlogx
Differentiating both sides with respect to x, we obtain
u
1
dx
du
=logx.
dx
d
(x)+x.
dx
d
(logx)
⇒
dx
du
=u[logx.1+x
x
1
]
⇒
dx
du
=x
x
[logx+1]=x
x
(1+logx) .....(2)
v=x
a
∴
dx
dv
=
dx
d
(x
a
)
⇒
dx
dv
=ax
a−1
.....(3)
w=a
x
⇒logw=loga
x
⇒logw=xloga
Differentiating both sides with respect to x, we obtain
w
1
.
dx
dw
=loga.
dx
d
(x)
⇒
dx
dw
=wloga
⇒
dx
dw
=a
x
loga .....(4)
s=a
a
Since a is constant, a
a
is also a constant.
∴
dx
ds
=0 .....(5)
From (1), (2), (3), (4) and (5) we obtain
dx
dy
=x
x
(1+logx)+ax
a−1
+a
x
loga+0
=x
x
(1+logx)+ax
a−1
+a
x
loga
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.